Beyond the market : the social foundations of economic efficiency - Beckert, Jens (Princeton : Princeton University Press, 2002)
Launches a sociological investigation into economic efficiency. Prevailing economic theory, which explains efficiency using formalized rational choice models, often simplifies human behavior to the point of distortion. This work finds such theory to be particularly weak in explaining such crucial forms of economic behavior as cooperation, innovation, and action under conditions of uncertainty.
Includes bibliographical references (p. [327]-346) and index.
oif 23/04/15
Loans
Keywords: Decision making--Social aspects; Economics--Sociological aspects; Political science; Social sciences; Economics; Decision making